The summer job - Dent, Lizzy (G.P. Putnam's Sons, 2021)
Everyone imagines running away from their life at some point. But Birdy has actually done it-- and the life she has run to belongs to her best friend Heather. The only problem: she hasn't told Heather. But the summer job at the highland Scottish hotel that her world class wine-expert friend ditched turns out to be a lot more than Birdy bargained for. Can she survive a summer pretending to be her best friend? And can Birdy stop herself from falling for a man who thinks she's someone else? -- adapted from back cover.